SIS3 alleviates cisplatin-induced acute kidney injury by regulating the lncRNA Arid2-IR-transferrin receptor pathway - Jiayan Huang; Weiyan Lai; Ming Li; Canming Li; Tanqi Lou; Hui Peng; Zengchun Ye (Karger Publishers, 2022)
Introduction: TGF-β/Smad3 may be involved in the pathogenesis of acute kidney injury (AKI), but its functional role and mechanism of action in cisplatin-induced AKI are unclear. Here, we established a cisplatin-induced AKI mouse model to demonstrate that Smad3 may have roles in cisplatin nephropathy because of its potential effects on tubular epithelial cell (TEC) death and regeneration. Methods: Using a cisplatin-induced AKI model, the expression levels of lncRNA Arid2-IR were measured by qRT-PCR and the location detected by FISH. Transfected with overexpression lncRNA Arid2-IR by lentiviral vector in TECs, and the expression of Cleaved Caspase-3, Bax, Bcl-2, PCNA, P21, P27, TFRC, FTH and FTL were measured by western blot. Protein molecules bound to lncRNA Arid2-IR were identified by RIP, RNA pull-down assay, mass spectrometry. Results：LncRNA Arid2-IR was significantly downregulated in vivo and in vitro. SIS3 decreased cell apoptosis and promoted cell regeneration by upregulating lncRNA Arid2-IR expression. LncRNA Arid2-IR regulated the cell cycle by decreasing expression of the cyclin dependent kinase inhibitors P21 and P27. Finally, lncRNA Arid2-IR interacted with the transferrin receptor (TFRC), overexpression of lncRNA Arid2-IR increased TFRC expression and decreased FTH and FTL. Conclusion：Smad3 regulated lncRNA Arid2-IR via TFRC, thereby regulating the cell cycle, protecting against cell apoptosis and promoting cell regeneration.